An Italian survey of opioids misuse: Epidemiological and psychopathological aspects. (2021) - Stigliano, Gianfranco; Miuli, Andrea; Lalli, Aliseo; Alessi, Maria Chiara; Sociali, Antonella; Esposito, Fabiana; D'Angelo, Laura; d'Andrea, Giacomo; Mosca, Alessio; Santovito, Maria Chiara; Martinotti, Giovanni; di Giannantonio, Massimo
Abstract: Objective: Opioid abuse is a worrying reality especially in the US. The increase in the prescription of opioids in Europe poses the risk of a possible increase in the number of abusers also in Italy. The aim of the study is to evaluate the abuse of opioids in the youth population and to evaluate possible correlations with some psychopathological aspects. Methods: A survey, conducted from July 2019 to March 2020, about the use of opioids was spread to a group of subjects aged between 18 and 40 years. A socio-demographical investigation and psychometric scales evaluating internet game addiction, gaming online, quality of life and general psychometric features were administrated. Results: Nine-hundred and thirteen subjects completed the survey. Seventeen-five subjects (8.21%) have used one opioid at least once in their lifetime. Weak correlations were found between codeine and morphine intensity of use and sleep disturbance, cigarette smoked per day, while codeine correlates with the number of coffees taken per day and somatization. Conclusion: Although the data of this survey do not show high percentages of use in Italy (8.21% of the sample have used one of the listed opioids at least once in their lifetime), the correlations founded confirm the literature data already present highlighting the need for constant monitoring of this phenomenon.